2022
DOI: 10.25273/set-up.v1i1.13439.74-83
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Postur Kerja Dengan Metode REBA Untuk Mengurangi Keluhan Musculoskeletal Pada Petani Padi Di Desa Sugihrejo Magetan

Abstract: Petani di Desa Sugihrejo Kecamatan Kawedanan Kabupaten Magetan masih menggunakan cara tradisional dalam melakukan pekerjaannya artinya masih menggunakan tenaga fisik dibandingkan menggunakan alat-alat modern. Seperti menggunakan cangkul saat menggarap sawah dibandingkan menggunakan traktor. Dari hasil penelitian posisi kerja petani saat menanam padi yaitu membungkuk dan berdiri. Posisi kerja ini sangat tidak ergonomis karena dapat mengakibatkan punggung, pinggang, leher, lengan, dan kaki petani menjadi cepat m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…The results of a study by Hidayati who analyzed correlation between working postures and low back pain complaints showed that there was a correlation between low back pain and working postures. The finding is supported by the theory by Tarwaka et al (2004) regarding ergonomy for Safety, Health, and Productivity that non-ergonomic postures would have non-low risk of back pain (Setyawan et al, 2022).…”
Section: Work Posture Of Railway Track Raisingsupporting
confidence: 62%
“…The results of a study by Hidayati who analyzed correlation between working postures and low back pain complaints showed that there was a correlation between low back pain and working postures. The finding is supported by the theory by Tarwaka et al (2004) regarding ergonomy for Safety, Health, and Productivity that non-ergonomic postures would have non-low risk of back pain (Setyawan et al, 2022).…”
Section: Work Posture Of Railway Track Raisingsupporting
confidence: 62%